2014
DOI: 10.1016/j.jhep.2014.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B flares in chronic hepatitis B: Pathogenesis, natural course, and management

Abstract: Hepatitis B flare, defined as an event with abrupt rise of alanine aminotransferase (ALT) levels to >5 times the upper limit of normal during chronic hepatitis B virus (HBV) infection, is considered to be the result of a human leukocyte antigen-I restricted, cytotoxic T lymphocyte mediated immune response against HBV and its downstream mechanisms. It may occur spontaneously, during or after antiviral therapy and in the setting of immunosuppression and/or chemotherapy. The clinical spectrum of hepatitis B flare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
255
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(279 citation statements)
references
References 94 publications
8
255
6
1
Order By: Relevance
“…It is conceivable that the Axl feedback regulatory pathway as induced by excessive IFN-α/β signaling during early stage of HBV infection sets the stage for relaying subsequent HBVtolerant immune responses. The immune tolerizing machinery following Axl signaling that maintains the HBV-tolerant state at later stage is currently open for further investigation.Our findings seem contradictory to current clinical practice where IFN-α is used for treating chronic HBV infection [32][33][34]. The paradox can be reconciled by the fact that enhanced IFN-α/β expression of the young mice in our model occurs at an early stage of HBV infection.…”
contrasting
confidence: 84%
“…It is conceivable that the Axl feedback regulatory pathway as induced by excessive IFN-α/β signaling during early stage of HBV infection sets the stage for relaying subsequent HBVtolerant immune responses. The immune tolerizing machinery following Axl signaling that maintains the HBV-tolerant state at later stage is currently open for further investigation.Our findings seem contradictory to current clinical practice where IFN-α is used for treating chronic HBV infection [32][33][34]. The paradox can be reconciled by the fact that enhanced IFN-α/β expression of the young mice in our model occurs at an early stage of HBV infection.…”
contrasting
confidence: 84%
“…In addition, DEG-GO network obtained from IT-IA patients revealed that most important GO terms were involved in immune response ( Figure 5). Spontaneous hepatitis flare (acute exacerbations) with sudden elevation of serum ALT over five times the upper limit of normal or a greater than 3-fold increase in ALT are often hallmarks of the immune clearance phase (30,31). Previous studies have revealed that immune response against HBV antigens mediated by HLA-class I antigen-restricted, cytotoxic T lymphocyte (CTL) and its downstream mechanisms can cause the hepatitis flares.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of studies have demonstrated that a variety of regulatory molecules participate in immune response, contributing to chronic HBV infection, dysregulated liver inflammation and disease progression [10,11]. A better understanding of the role of immune factors in the pathogenesis of HBV infection will shed new light on the mechanisms of HBV-infected liver diseases and provide new therapeutic target for anti-HBV treatment.…”
Section: Discussionmentioning
confidence: 99%